Middle leading small-scale school projects. Issue 7 (29th August 2019) - Grootenboer, Peter; Larkin, Kevin
Abstract : Purpose: The authors argue that middle leaders are the key educators in school-based educational development. Schools often secure small-scale funding to engage in government or systemic initiatives, and these projects require a leadership "close to the classroom" if they are to realise sustainable educational gains. This leadership often comes from the middle leaders – those who practice their leading in and around classrooms. The paper aims to discuss this issue. Design/methodology/approach: A single case study methodology is used to investigate two middle leaders, leading a small-scale project. Their leading practices are examined using the "theory of practice architectures", to identify how these practices were enacted within their educational context. Findings: While principals play a crucial role in enacting change, it is the middle leaders who are closer to the classroom than most principals, and whose practices more directly impact teaching and learning as they are best placed to ensure that meagre resources are well used to improve student learning. They do this by ensuring that development is collegial and a response to evidence-based needs. Practical implications: First, middle leaders need support in facilitating educational development. Second, their leading practice is crucial for sustainable school-based development. Third, site-based educational development occurs most effectively when it is evidence-based. Finally, this form of educational development requires high-level collegiality. Originality/value: This paper is original in two key ways: first, it addresses the under-researched practices of middle leaders; and, second it employs the practice theory to understand school leadership and development.